2017
DOI: 10.1007/s40279-017-0777-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Interval Training on Fitness, Fat Mass and Cardiometabolic Biomarkers in Children with Obesity: A Randomised Controlled Trial

Abstract: Clinicaltrials.gov; NCT01991106.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
1
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(153 citation statements)
references
References 49 publications
4
135
1
13
Order By: Relevance
“…Other studies of lifestyle intervention in children and adolescents in Australia, have reported a similar drop-out rate [39,51]. The aforementioned Australian trial of HIIT versus MICT in children with obesity had higher exercise session attendance rates (average 68%); however, it demonstrated a similar trend to GRIT for reduction in attendance rates across its 12-week program [39]. The other previously noted study which assessed the feasibility of HIIT in adults in a real-world setting had an attendance rate of 59% in their aerobic interval training group, which is similar to the attendance rates at exercise sessions for GRIT completers.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Other studies of lifestyle intervention in children and adolescents in Australia, have reported a similar drop-out rate [39,51]. The aforementioned Australian trial of HIIT versus MICT in children with obesity had higher exercise session attendance rates (average 68%); however, it demonstrated a similar trend to GRIT for reduction in attendance rates across its 12-week program [39]. The other previously noted study which assessed the feasibility of HIIT in adults in a real-world setting had an attendance rate of 59% in their aerobic interval training group, which is similar to the attendance rates at exercise sessions for GRIT completers.…”
Section: Discussionsupporting
confidence: 58%
“…Attendance at program sessions was lower than the expected target of 80% and over one third of participants withdrew from the program. Other studies of lifestyle intervention in children and adolescents in Australia, have reported a similar drop-out rate [39,51]. The aforementioned Australian trial of HIIT versus MICT in children with obesity had higher exercise session attendance rates (average 68%); however, it demonstrated a similar trend to GRIT for reduction in attendance rates across its 12-week program [39].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Exercise, a sub-component of physical activity that is carried out to sustain or improve health, has frequently been utilised to improve physical health (Anderson et al, 2016;Farina, Rusted, & Tabet, 2014;Haskell, Lee, Pate, Powell, & Blair, 2007;Janssen & LeBlanc, 2010). Within children and adolescents, research has shown that prescribing exercise, such as resistance or interval training, can significantly improve physical activity levels and mitigate the risk of health issues such as type 2 diabetes mellitus, cardiovascular disease and obesity (Dias et al, 2017;Shiroma et al, 2017;K. L. Weston et al, 2016).…”
Section: Exercisementioning
confidence: 99%